(sec^2 B - 1)(cot^2 B + 1) = sec^2 B

### 1 Answer | Add Yours

It has to be shown that `(sec^2 B - 1)(cot^2 B + 1) = sec^2 B`

`(sec^2 B - 1)(cot^2 B + 1)`

=> `(sec^2 B*cot^2 B + sec^2 B - cot^2 B - 1`

=> `(1/(cos^2B))*(cos^2B)/(sin^2B) + 1/(cos^2B) - (cos^2B)/(sin^2B) - 1`

=> `1/(sin^2B) + 1/(cos^2B) - (cos^2B)/(sin^2B) - 1`

=> `(sin^2B)/(sin^2B) + 1/(cos^2B) - 1`

=> `1 + 1/(cos^2B) - 1`

=> `sec^2B`

**This proves that: **`(sec^2 B - 1)(cot^2 B + 1) = sec^2 B `

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes